Climate Change, Floods, and Community Resilience: A Study of the Kamala River Basin, Nepal - Chandra Lal Pandey (Journal of Flood Risk Management, 2025)
ABSTRACT Climate change is one of the biggest threats humanity is facing in the 21st century. Nepal, being a low‐income country located on the lap of the Himalayas, is experiencing a wide range of impacts from changing climate and climate‐induced disasters. Communities of the Kamala river basin are increasingly affected by climate‐induced hazards such as floods. Land use change, deforestation, and climate change‐induced disasters such as landslides, droughts, and floods are affecting the riverine communities. Floods have been one of the most serious threats for centuries; however, their frequency and scope are being amplified by climate‐induced extreme weather events. Employing a convergent mixed‐method approach, this study explored the impacts of climate‐induced disasters, especially focusing on floods in Ward 12 of Siraha and Ward 11 of Dudhauli municipalities in Nepal's Kamala river basin. It investigated the current status of impacts of climate change‐induced disasters; the availability, usage and effectiveness of flood early warning systems; and analyzed local community practices for making communities flood and disaster resilient. The findings suggested that the climate‐induced disasters are becoming key concerns for the communities as they are affecting multiple areas from water security to livelihood options. In addition, the existing early warning systems for floods are still weak. While communities are attempting adaptation strategies including increasing social cohesion, their resilience level is insufficient. This study has made original contribution to the relevant literature and developed applicable knowledge for strengthening local communities' capacities to build climate, flood, and disaster resilience.